ANALYSIS OF A STEGANOGRAPHIC METHOD FOR HIDING ONE IMAGE IN ANOTHER IMAGE USING MATLAB AND IMAGE PROCESSING TOOLBOX: ANALYSIS OF A STEGANOGRAPHIC METHOD FOR HIDING ONE IMAGE IN ANOTHER IMAGE USING MATLAB AND IMAGE PROCESSING TOOLBOX - Denev, Daniel (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Analysis of a Steganographic Method for Hiding an Image into a Cover Image Using MATLAB and Image Processing Toolbox: The paper presents an algorithm for hiding a 24-bit color image in bmp format in another 24-bit color image also in bmp format. The algorithm is based on the least-significant bit method and is implemented using MATLAB and Image Processing Toolbox. This algorithm can be applied for 100% reconstruction of the hidden image when four cover images are used.